ISOLASI DAN IDENTIFIKASI BAKTERI Aeromonas sp. DARI LELE DUMBO (Clarias sp.) DI KABUPATEN NGAWI - Sri Rejeki; Triyanto Triyanto; Murwantoko Murwantoko (Universitas Gadjah Mada, 2016)
African catfish (Clarias sp.) is one of important freshwater fish which prefer consumed by people due to many advantages. Aeromonas sp. bacteria are dangerous patogen for freshwater fishes. This objective of the research was to isolate, identify and determine pathogenicity of Aeromonas sp. bacteria from African catfish from District Ngawi. The samples of catfish with 20 - 25 cm length showing clinical signs disease were obtained from three sub districts. Bacteria were isolated from kidney and inoculated into GSP medium. Characterization and identification through morphology of bacterial colonies, cells and biochemical test. Postulate Koch was conducted to verify abaility to couse disease. Pathogenicity was analyzed by determination of value of Lethal Dosage-50 on catfish on 7 - 9 cm length. The result showed that the disease symptoms of fish infected by the bacteria were skin ulcer, abdominal swelling and kidney damage. Fifteen bacterial isolates were collected which five, six and four isolates were from Kecamatan Karang Jati, Geneng dan Paron.sub-district respectively. The result showed 12 isolates (GKJ1, GKJ3, GKJ4, GGN1, GGN2, GGN3, GGN4, GGN5, GGN6, GPR2, GPR3 and GPR4) were identified as Aeromonas hydrophila. Three isolates (GKJ2, GKJ5 and GPR1) were identified as A. salmonicida. Isolate of A. hydrophila GKJ1, GKJ4, GGN2, GGN5, GPR2 and GPR4 were virulent to African catfish with LD50 values of 1,55 x 105, 3,89 x 105, 7,24 x 105, 2,39 x 105, 6,61 x 104 and 1,95 x 104 cfu/fish.